Fulminant leptomeningeal disease diagnosed as comutant H3F3A and FGFR diffuse midline glioma - Benistant, Larysa; Reita, Damien; Schenck, Maleka; Castelain, Vincent; Cebula, Hélène; Lhermitte, Benoît; Bender, Laura (Annals of clinical and translational neurology, 2024)
Diffuse midline gliomas present a particularly intricate and challenging clinical scenario. This rare case involves a patient with comutant H3F3A and FGFR diffuse midline glioma with a clinical presentation of fulminant leptomeningitis. A 22‐year‐old male presented with fatal and fulminant diffuse leptomeningitis. Next‐generation sequencing of plasma and cerebrospinal circulating tumour DNA revealed diffuse midline gliomas with H3F3A and FGFR mutations. Methylome analysis of meningeal tissue collected during autopsy confirmed the diagnosis. Liquid biopsy plays a crucial role in the diagnosis of diffuse midline gliomas, mainly those with exclusively leptomeningeal presentations.